Studies on deaf mobile application - Nathan, Shelena Soosay; Hussain, Azham; Hashim, Nor Laily (2016)
The deaf normally considered to be disabled that do not need any mobile technology due to the inabilities of hearing and talking.However, many deaf are using mobile phone in their daily life for various purposes such as communication and learning.Many studies have attempted to identify the need of deaf people in mobile application and level of usage of the applications. This study aims in studying the recent research conducted on deaf mobile application to understand the level of importance of mobile technology for this disabled community.This paper enable identification of studies conducted are limited and the need of more research done of this disabled people to ensure their privilege of using mobile technology and its application, which leads to the identification of deaf user requirement for mobile application as future study.